Antholoba fabiani sp. nov. (Actiniaria, Metridioidea, Antholobidae fam. nov.), a new species and family of sea anemone of the southwestern Atlantic, Brazil - Durán-Fuentes, Jeferson A. [UNESP]; González-Muñoz, Ricardo; Daly, Marymegan; Stampar, Sérgio N. [UNESP] (Springer Nature, 2024)
The genus Antholoba Hertwig, 1882 (Actiniaria, Enthemonae) is characterized by the presence of short and numerous tentacles, a folded oral disc in lobes or cup-shaped with an expanded distal part, transversely wrinkled body wall surface, a very long mesogloeal sphincter, parietobasilar muscles poorly developed, and the absence of acontia. Currently, the genus Antholoba is classified within the family Actinostolidae Carlgren, 1893 (superfamily Actinostoloidea Carlgren, 1932) and comprises two valid species: A. achates (Drayton in Dana, 1846) which have been recorded in Antarctica, the southwestern Atlantic, and the southeastern-western Pacific; and A. perdix (Drayton in Dana, 1846) which is distributed in the northwestern Atlantic, including the Gulf of Mexico. In recent collections along Ubatuba Bay in northern São Paulo, Brazil, we found specimens of a third, unknown species, which exhibits morphological and genetic differences from the only other species recorded from that place, A. achates (Drayton in Dana, 1846). Additionally, we examined five specimens of A. achates collected in Penha, Santa Catarina State, for morphological comparison. Our phylogenetic analyses, using molecular data, affirm the difference between the two species. Furthermore, the resultant phylogenetic trees recover the species of the genus Antholoba as a sister group to the acuticulate clade, within the superfamily Metridioidea, instead of within Actinostoloidea. We describe the material from Ubatuba as a new species, A. fabiani sp. nov., providing information and photographs of its external and internal anatomy, as well as cnidom, along with sequences of mitochondrial (12S, 16S, and COIII) and nuclear (18S and 28S) markers. Additionally, we propose placing the genus Antholoba within Metridioidea, and introduce the new family Antholobidae fam. nov.
Keywords: Actinostoloidea; Anthozoa; Benthic invertebrate fauna; Cnidaria; Hexacorallia